An Embedded Controller for Greenhouse Shade Curtain - Dogra, A K; Parsad, K; Suri, Kapil; Kumar, Narendra (Journal of Agricultural Engineering, 2004)
A microprocessor based environment control system has been envisaged for greenhouses. Light control has been selected for this study. The controller will not only control the solar radiations but also indirectly, achieve a temperature balance inside the greenhouse. The automatic shading curtain has been designed using off the shelf components, with an 8-bit RISC micro-controller. An 8-bit AVR RISC controller 1K Byte Flash (ATtiny 15L) manufactured by ATMEL. The controller is designed to sense the light intensity and based on set limits it actuates a control motor to operate shade curtain open or close. The shade curtain is coupled mechanically with shade cloth mounting system.